Do Enamelin, Lactotransferrin, and Amelogenin-X Polymorphisms Predispose Dental Caries Susceptibility in Egyptian Children? A Cross-Sectional Study - Hassan Mossad Hassan Negm (Taylor & Francis Group, 2023)
ABSTRACTObjective The secretion of salivary immune factors and the accumulation of nonimmune elements represent the first line of oral immunity defense against cariogenesis. As the interplay between genetic and environmental predisposing factors in inducing dental caries is controversial, we investigated the association between three genetic polymorphisms in Egyptian children.Method Our genetic network analysis demonstrated that AMELX, ENAM, LTF, MEPE, BMP2, BMP4, IFNG, IL6, TNF, PROM1, TUFT1, and CDKN1A play a critical role in promoting an anti-cariogenic effect in different ethnic groups. Enamelin, lactotransferrin, and amelogenin-X (AMELX) exon-intron boundaries were sequenced in 148 patients with extensive caries (n = 74) or caries-free patients (n = 74) from different Egyptian hospitals.Results The presence of specific genetic polymorphisms, namely ENAM rs3796703, AMELX rs946252, and LTF rs1126478, showed a significant association with increased susceptibility to dental caries within the caries-susceptible group. These particular polymorphisms exhibited a noteworthy presence or occurrence rate in individuals who were more prone to developing dental caries.Conclusion ENAM rs3796703, AMELX rs946252 were frequently detected in the caries-susceptible group, suggesting the possible correlation between the defect in these proteins and the incidence of developing dental caries. The polymorphisms in LTF rs1126478 were related to a high DMFT index (≥7) among Egyptian children.